Implementasi Pendidikan Multikultural Untuk Menanamkan Nilai Toleransi Dalam Kelas Inklusi Di Sekolah Dasar - Zahra, Camila Aulia Az; Muttaqin, Muhammad Fauzan (CV. SINAR HOWUHOWU, 2025)
This research seeks to examine how multicultural education is applied to promote tolerance in inclusive classrooms in primary schools. Multicultural education is crucial within the context of diversity in Indonesia, particularly in elementary schools where students come from various cultural, religious, and ability backgrounds, including those with special needs. To meet this goal, this research utilized a literature review approach, which included gathering, examining, and synthesizing a range of pertinent scientific materials, including domestic and global journals, reference books, and earlier research results. The data were examined through a descriptive-qualitative lens, leading to both a theoretical and practical comprehension of how multicultural education is applied in inclusive elementary schools. The findings suggest that multicultural education is crucial in fostering values of tolerance, empathy, fairness, and mutual respect in students. By adopting methods like integrating diversity principles into the curriculum, using cooperative learning, fostering intercultural engagement, and promoting project-based initiatives, educators can create a classroom environment that appreciates diversity. The research indicates that there are contributing elements like teacher preparedness, inclusive educational policies, and the implementation of diversity-focused learning resources. Nonetheless, challenges exist such as teachers' insufficient comprehension of multicultural education, inadequate supporting resources, and minimal community engagement. This study validates that the adoption of multicultural education in inclusive classrooms is a proactive measure to promote tolerance among elementary school students. These initiatives need to be implemented in a systematic and ongoing way to effectively address the obstacles presented by diversity in education.